The Effects of Additional Radial Shock Wave Therapy on Spasticity of Upper Extremity Muscle - Go Linda Sugiarto; Tanti Ajoe Kesoema (Surabaya Physical Medicine and Rehabilitation Journal, 2023)
Background: Spasticity is one of the most common problems and greatly interferes with the functional capacity of chronic stroke patients. The most commonly used treatments are infrared therapy and stretching exercises, but they have not reduced spasticity effectively. The addition of Radial Shock Wave Therapy (RSWT) was expected to be more effective in reducing spasticity in chronic stroke patients.  Aim: The purpose of this study is to prove that the addition of RSWT is more effective reducing spasticity of chronic stroke patients. Material and methods: This study was a simple randomized controlled pre- and post-experimental design. The total sample of 30 chronic spastic stroke patients with the Modified Asworth Scale 2-3 was divided into 2 groups: the study group and the control group. RSWT was provided once a week to the muscle belly of the flexor wist muscle on the ventral aspect of the forearm, the intrinsic muscle of the hand, and flexor digitorum tendon. They were added to infrared therapy and stretching exercises in the upper extremities which are provided three times a week for six weeks consecutively. The level of spasticity was measured by the Tardieu Scale, which measures quality and angle of resistance at the beginning and end of the study. Results: A significantly greater reduction was obtained (p<0.05) from the level of spasticity measured by the Tardieu Scale, both on the quality and angle of resistance, in the study group. Conclusion: The addition of RSWT has been shown to have a greater reduction in spasticity in upper extremity muscle in chronic stroke patients.